2019
DOI: 10.17161/kjm.v12i4.13262
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport after Surgical Treatment of Lisfranc Injuries in Athletes: A Retrospective Case Series

Abstract: Introduction A Lisfranc injury can be a devastating injury in athletes,and if inadequately treated, may lead to chronic pain and lossof function. The purpose of this study was to determine the rate andtime until return to sport after surgical fixation for a ligamentous Lisfrancinjury. We hypothesized that open reduction and screw fixationof a ligamentous Lisfranc injury can be a successful treatment in theathletic population and allow patients to return to sport at close totheir preinjury level of play.&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…The literature strongly supports the idea that prompt and appropriate treatment of Lisfranc sports injuries causes most patients to return to their athletic activities [58]. Studies have consistently shown that individuals who receive proper treatment for these injuries can typically resume their activities within a mean timeframe of 28-35 weeks [58]. Moreover, they often achieve a level of performance comparable to their pre-injury status.…”
Section: Return To Play After Lisfranc Sports Injuriesmentioning
confidence: 90%
“…The literature strongly supports the idea that prompt and appropriate treatment of Lisfranc sports injuries causes most patients to return to their athletic activities [58]. Studies have consistently shown that individuals who receive proper treatment for these injuries can typically resume their activities within a mean timeframe of 28-35 weeks [58]. Moreover, they often achieve a level of performance comparable to their pre-injury status.…”
Section: Return To Play After Lisfranc Sports Injuriesmentioning
confidence: 90%
“…This finding is surprising, given the general belief that Lisfranc injuries have the potential to end athletic careers and result in chronic pain and loss of function. 21 Previous studies reporting on RTP after a Lisfranc injury in athletes have had similar or lower sample sizes. 2 , 11 , 16 , 18 , 21 Most Lisfranc injuries were experienced by offensive linemen (n = 8; 24.2%), followed by running backs (n = 7; 21.2%).…”
Section: Discussionmentioning
confidence: 99%
“… 21 Previous studies reporting on RTP after a Lisfranc injury in athletes have had similar or lower sample sizes. 2 , 11 , 16 , 18 , 21 Most Lisfranc injuries were experienced by offensive linemen (n = 8; 24.2%), followed by running backs (n = 7; 21.2%). The median RTP time was 11.0 months (IQR, 10.2-11.8).…”
Section: Discussionmentioning
confidence: 99%
“…Further to the inconsistent radiographic diagnostic criteria observed, there were studies excluded during the literature search because these studies reported radiographic indications for surgery rather than diagnostic criteria [51][52][53]. The decision to exclude these studies was based on the fact that indication for surgery is inherently different from diagnosis criteria.…”
Section: Discussionmentioning
confidence: 99%